A Nearly Accurate Solar Photovoltaic Emulator Using a dSPACE Controller for Real-time Control. Issue 7 (20th April 2016) - Azharuddin, Mohammed; Babu, Thanikanti Sudhakar; Bilakanti, Nishant; Rajasekar, Natarajan
Abstract: A nearly accurate solar photovoltaic emulator using DC-DC buck converter is proposed. A mathematical model developed using MATLAB/SIMULINK (The MathWorks, Natick, Massachusetts, USA) serving as reference is built for emulating solar photovoltaic characteristics. Hardware implementation is done using a dSPACE ds1104 controller board (dSPACE GmbH, Paderborn, Germany), and a closed-loop control system is constructed using proportional integral (PI) controller. The proposed emulator has the following characteristics:(1) faster dynamic response with easy interfacing, (2) the advantage of real-time control, (3) a DC-DC buck converter with higher bandwidth, (4) highly stable output with lower response time, and (5) lower output voltage and current ripple. Experimentations are done under different operating conditions, and the results obtained are presented. Further, to demonstrate the capability of the proposed emulator, maximum power point tracking using the hill-climbing method is tested on a DC-DC boost converter interfaced to the solar photovoltaic emulator.